2019
DOI: 10.1007/s40094-019-0318-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined laser dyes on the efficiency of cholesteric liquid crystal lasers

Abstract: A high efficiency band-edge cholesteric liquid crystal (CLC) laser comprising an optimal binary-dye mixture (OBD) with 62 wt% DCM and 38 wt% PM597 as the active medium is scrutinized. The measurements indicate that both the fluorescence spectrum width and the order parameter of OBD in the host of nematic liquid crystal (BL009) enhance compared with those for each individual dye. Furthermore, at the fluorescence peak, the optical efficiency of the PM597-doped CLC laser is ~ 1.5× higher than that of DCM, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Therefore, as the dopant concentration increases in the CLC droplet, the absorption of the dye molecules in CLC increases accordingly, leading to optimal performance of CLC lasers. 55 To demonstrate that absorption strength plays a dominant role in lasing wavelength shifting, here we used two dyes (B2 and NR) to explain this phenomena. As shown in Figure 3b,d, we experimentally measured the absorption and emission cross section of B2-and NR-doped CLC droplets under different chiral dopant concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as the dopant concentration increases in the CLC droplet, the absorption of the dye molecules in CLC increases accordingly, leading to optimal performance of CLC lasers. 55 To demonstrate that absorption strength plays a dominant role in lasing wavelength shifting, here we used two dyes (B2 and NR) to explain this phenomena. As shown in Figure 3b,d, we experimentally measured the absorption and emission cross section of B2-and NR-doped CLC droplets under different chiral dopant concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The bottom panel of Figure a illustrates the pitch variation of the dye-doped liquid crystal matrix under low and high dopant concentration in CLC droplet. Therefore, as the dopant concentration increases in the CLC droplet, the absorption of the dye molecules in CLC increases accordingly, leading to optimal performance of CLC lasers …”
Section: Results and Discussionmentioning
confidence: 99%
“…By virtue of this combination, a single UV pumping beam could be used to achieve simultaneous lasing at the red and green wavelengths where the long-wavelength band edges were placed [ 1 , 25 ]. In addition, the transition dipole moments of the DCM and C540A dyes held positive-order parameters when situated within the liquid crystal (LC) hosts [ 26 , 27 ]. This indicated that the orientation of these transition dipole moments was aligned with the local molecular alignment within the LC molecules, which gave rise to greater overlap between the transition dipole moment of dye molecules and the polarization vector of the incident electromagnetic wave [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as dopant concentration increases in the CLC droplet, the absorption of the dye molecules in CLC increases accordingly, leading to optimal performance of CLC lasers. 184 To demonstrate that absorption strength plays a dominant role in lasing wavelength shifting, here four distinct dyes (B2, NR, C6, and DCM) were used to explain this phenomenon. As shown in Figure 4.20 (a-d), the absorption and emission cross-section of B2-, NR-, C6-, and DCM-doped CLC droplets were experimentally measured under different chiral dopant concentrations.…”
Section: Theoretically Calculationmentioning
confidence: 99%